Augmented Cooper test: Biomechanical contributions to endurance performance - Apte, Salil; Troxler, Simone; Besson, Cyril; Gremeaux, Vincent; Aminian, Kamiar (Frontiers in Sports and Active Living, 2022)
Running mechanics are modifiable with training and adopting an economical running technique can improve running economy and hence performance. While field measurement of running economy is cumbersome, running mechanics can be assessed accurately and conveniently using wearable inertial measurement units (IMUs). In this work, we extended this wearables-based approach to the Cooper test, by assessing the relative contribution of running biomechanics to the endurance performance. Furthermore, we explored different methods of estimating the distance covered in the Cooper test using a wearable global navigation satellite system (GNSS) receiver. Thirty-three runners (18 highly trained and 15 recreational) performed an incremental laboratory treadmill test to measure their maximum aerobic speed (MAS) and speed at the 2nd ventilatory threshold (sVT2). They completed a 12-minute Cooper running test with foot-worm IMUs and a chest-worn GNSS-IMU on a running track 1-2 weeks later. Using the GNSS receiver, an accurate estimation of the 12-min distance was obtained (accuracy of 16.5m and precision of 1.1%). Using this distance, we showed a reliable estimation (R2 > 0.9, RMSE ϵ [0.07, 0.25] km/h) of the MAS and sVT2. Biomechanical metrics were extracted using validated algorithm and their association with endurance performance was estimated. Additionally, the high/low performance runners were compared using pairwise statistical testing. All performance variables, MAS, sVT2 and average speed during Cooper test, were predicted with an acceptable error (R2 ≥ 0.65, RMSE ≤ 1.80 kmh-1) using only the biomechanical metrics. The most relevant metrics were used to develop a biomechanical profile representing the running technique and its temporal evolution with acute fatigue, identifying different profiles for runners with highest and lowest endurance performance. This profile could potentially be used in standardized functional capacity measurements to improve personalization of training and rehabilitation programs.